Physicians in Supporting Roles: Time to Share the Spotlight. Issue 3 (20th November 2019) - Click, Benjamin
Abstract : With rising interest in multidisciplinary care models for inflammatory bowel disease, the optimal team arrangements, roles, and dynamics are unknown. This editorial comments on the importance of work addressing this issue in an inflammatory bowel disease patient-centered medical home model.